Analyzing Migration Restriction Regimes - Jasso, Guillermina (Frontiers in Sociology, 2021)
This paper develops a framework for analyzing migration restriction regimes, and illustrates it with the case of U.S. immigration law and policy. Nation-states regulate the entry of foreign-born persons, and this regulation comprises three elements: the type of restriction, the apparatus of restriction, and the consequences of restriction. Restriction may be based on personal characteristics, numerical ceilings, or both. Personal restriction notices the characteristics of persons, using them as criteria for granting or denying admission. Numerical restriction places numerical ceilings on admissions. The apparatus of restriction may stipulate specific ceilings, whether some groups are exempt from the ceiling and, if so, by what criteria, and whether admission under the ceiling is first-come/first-served or by lottery or instead preferential and, if so, by what criteria. Two unintended consequences follow immediately: unauthorized migration (under both personal and numerical restriction); and visa-number backlogs (under numerical restriction). These in turn generate a range of policy devices: border enforcement, procedures for legalization and deportation, and procedures for clearing backlogs. Indeed, the history of a country's immigration law may be understood as a sequence of measures for first setting up the apparatus of restriction and then altering it in order not only to re-examine provisions of the initial setup but also to address unauthorized migration and visa-number backlogs. Viewing migration through this lens enables assessment of particular legislation and, more broadly, dynamics of a migration restriction regime, subject to world circumstances, including its possible inherent instability. The migration restriction lens also generates new metrics for a country's attractiveness and its innovativeness and creativity. To illustrate, the paper examines the migration restriction regime in the United States since the country's founding. Finally, the paper provides a checklist for a migration restriction setup that doubles as the basis for table shells for summarizing a country's migration restriction regime and its history.